2018
DOI: 10.1016/j.devcel.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid Transfer Protein Signaling Axis Exerts Dual Control of Cell-Cycle and Membrane Trafficking Systems

Abstract: Kes1/Osh4 is a member of the conserved, but functionally enigmatic, oxysterol binding protein-related protein (ORP) superfamily that inhibits phosphatidylinositol transfer protein (Sec14)-dependent membrane trafficking through the trans-Golgi (TGN)/endosomal network. We now report that Kes1, and select other ORPs, execute cell-cycle control activities as functionally non-redundant inhibitors of the G/S transition when cells confront nutrient-poor environments and promote replicative aging. Kes1-dependent cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…Interestingly, members of the StARkin-related and Sec14 domain-containing (CRAL-TRIO) superfamilies of LTPs have been classically defined as PtdIns-transfer proteins (PITPs) that are thought to function by redistributing PtdIns from donor to acceptor membranes, likely as part of a heterotypic exchange involving additional lipid species such as phosphatidylcholine or phosphatidic acid (Cockcroft and Carvou, 2007; Grabon et al, 2019). Despite their name, it is yet to be understood how these PITPs function within intact cells; although unique PITPs are increasingly linked to specific signaling modalities in studies of model organisms (Xie et al, 2018; Huang et al, 2018). In addition to the autonomous PITPs, recent work has also suggested that PtdIns can be used as a lipid cargo by the relatively promiscuous TUbular LIPid-binding (TULIP) family of LTPs that possess synaptotagmin-like mitochondrial lipid-binding protein (SMP) domains; including a report of preferential PtdIns transfer from the ER to the PM by the SMP domain-containing protein TMEM24 following PLC activation and PtdIns(4,5)P 2 hydrolysis (Lees et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, members of the StARkin-related and Sec14 domain-containing (CRAL-TRIO) superfamilies of LTPs have been classically defined as PtdIns-transfer proteins (PITPs) that are thought to function by redistributing PtdIns from donor to acceptor membranes, likely as part of a heterotypic exchange involving additional lipid species such as phosphatidylcholine or phosphatidic acid (Cockcroft and Carvou, 2007; Grabon et al, 2019). Despite their name, it is yet to be understood how these PITPs function within intact cells; although unique PITPs are increasingly linked to specific signaling modalities in studies of model organisms (Xie et al, 2018; Huang et al, 2018). In addition to the autonomous PITPs, recent work has also suggested that PtdIns can be used as a lipid cargo by the relatively promiscuous TUbular LIPid-binding (TULIP) family of LTPs that possess synaptotagmin-like mitochondrial lipid-binding protein (SMP) domains; including a report of preferential PtdIns transfer from the ER to the PM by the SMP domain-containing protein TMEM24 following PLC activation and PtdIns(4,5)P 2 hydrolysis (Lees et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable development that has come from the Sec14 studies is that lipid transfer proteins function as an antagonistic pair in coupling PtdIns4P signaling with TGN/endosomal membrane trafficking. That is, the action of the pro-trafficking Sec14 is countered by the action of the Kes1/Osh4, a PtdIns4P/ergosterol exchange protein that functions as a trafficking brake in this system (23,146,149,(153)(154)(155)(156). Moreover, the antagonistic actions of Kes1 and Sec14 in TGN/endosomal membrane trafficking extend to cell cycle contexts associated with cellular commitment to a new round of cell division.…”
Section: The Antagonistic Relationship Of Sec14 With Lipid Exchange Pmentioning
confidence: 99%
“…Despite these studies, it is still not clear how PITPs function within intact cells, including whether they efficiently transport PtdIns or alternatively regulate PLC activity. In contrast, functional studies using more complex in vivo models have associated diverse PITPs with specific roles in membrane trafficking and signal transduction in defined cellular contexts . It has also been postulated that PITPs may contribute to the allosteric control of other membrane‐associated proteins or serve as modules for presenting bound PtdIns to modifying enzymes, with the most compelling evidence coming from yeast studies using Sec14 .…”
Section: Phosphatidylinositol Synthesis and Transportmentioning
confidence: 99%